Efeitos do lactofen no crescimento e produtividade da soja rr em diferentes condições edafoclimáticas - Rios, Fabiano Aparecido (2016)
The genetic evolution of cultivars together with management practices provide high yields when used correctly. However, they are not rare situations that lead to the soybean to excessive or reduced growth. In this contest, knowledge of the factors involved in selectivity herbidas, such as climate, soil and variety, are in many cases decisive for the success of the activity. Thus, the objective of this work was to study the effect of lactofen applied in different environmental conditions and soybean growth stages RR on growth and crop yield. Three experiments were conducted in different soil and climatic conditions. The first (Experiment 1) was installed in the city of Ivaiporã - PR in 2012/2013, with the variety of soy BMX Potência RR®. The treatments consisted of a control without application, a control without apical meristem, three doses of lactofen (60, 120 and 180 g ha-1), three doses of mepiquat chloride (50, 100 and 200 g ha-1) and lactofen + chorimuron ethyl (100 + 10.33 g ha-1), all applied at growth stage R1/R2. Experiments 2 and 3 were performed in the year 2013/2014 in the municipalities of Ivaiporã and Maringá - PR, respectively. The cultivar was BRS 360 RR®, both were installed in factorial (4 x 3) + 1, as follows: four doses of lactofen (60, 120, 180 and 240 g ha-1); three soybean growth stages at the time of herbicide application (V3/V4, V7/V8 and R1/R2); and an additional control without herbicide. In general all treatments caused phytotoxicity containing lactofen and reduced soybean growth, especially in higher doses. In soil and climate conditions for the growth of plants (Experiment 1) was lodging and yield reduction. In this situation, the application lactofen reduced growth and soybean lodging, increased stem lignin, and at a dose of 180 g ha-1 gave higher productivity than the control. When applied early in the development of soybean, BRS 360 RR®, lactofen (60 to 240 g ha-1) caused a transient reduction in plant growth without, however, affecting productivity. When the application was conducted in V7/V8 and predating water stress period (Experiment 2), doses of 180 and 240 g ha-1 lactofen, provided phytointoxication more persistent and caused revenue loss of culture. In non-stringent conditions (Experiment 3), only the dose of 240 g ha-1 lactofen applied early in the development of culture, caused reduced productivity. Thus, an excessive soybean growth conditions, lactofen applied at the beginning of the reproductive stage, at a dose of 180 g ha-1 prevents the drop in productivity caused by lodging and may be used as a growth regulator. In addition, high doses of lactofen together with water stress situations increase the persistence of plant injury and cause of soybean yield loss.